Frequency of pornography use is indirectly associated with lower relationship confidence through depression symptoms and physical assault among Chinese young adults - Conner, Stacy R. (Kansas State University, 2014)
Using data from young adults (N = 224) living in Beijing and Guangzhou, China this study examined the direct association between frequency of pornography use and relationship confidence and indirect associations through depression symptoms and physical assault. Results using structural equation modeling demonstrated that higher frequency of pornography use was indirectly linked with lower relationship confidence via depression symptoms and physical assault. These findings are informed by Social Constructionist Theory (Gergen, 1985), which considers how individuals take what they understand from their culture, exposure to material such as pornography, and other social experiences to develop and make meaning of who they are within their relational context.
Keywords: Couple outcomes; Depression; Physical assault; Pornography; Relationship confidence; Individual & Family Studies (0628)